EPICURO Vida, doctrinas morales, testimonios (HyA, 2002)
Otros autores: CORIA, Marcela; FASCIOLO, Pablo; FIGUEROA, Lidia Elisa; LEWIS, Juan Pablo; MAZZIOLI, Martina; NAVARRO, Fernando; RISTORTO, Marcela; SOLODKOW, David